Models of Feminism: Tunisia’s Opportunity to Overcome the Secular/Islamist Binary - Feldman, Jan (Hawwa, 2015)
As Tunisians publicly debate the roles of Islam, democracy and feminism in the post-revolutionary period, an opportunity has arisen for the historically fractured women’s movement to overcome the religious/secular “binary” that has crippled both Tunisian politics and the women’s movement for nearly six decades. For religious women, particularly those who are not members of their nation’s privileged elite, religion provides a vehicle for emerging from civil society and achieving political voice. The electoral showing of the Islamist Ennahdha party brought religious women into the constitutional debates and, therefore, into public conflict with secular women activists. While occasionally acrimonious, nonetheless, the public airing of mutual suspicions and grievances under the rubric of “Transitional Justice” is ripe with possibilities for reconciliation between the religious and secular factions of Tunisia’s women’s rights movement and perhaps society at large.